2021
DOI: 10.3390/su131810374
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between Variable and Constant Refrigerant Flow Air Conditioning Systems in Arid Climate: Life Cycle Cost Analysis and Energy Savings

Abstract: All over the world, there is a call to encourage sustainable energy thinking and implementation. There is an urgent need to consider sustainable solutions in any design projects that are able to reduce energy consumption. In the heating, ventilation, and air conditioning field, the rise of the variable refrigerant flow systems has made big progress. This study presents a life cycle cost analysis to evaluate the economic feasibility of constant refrigerant flow (CRF), and in particular, the conventional ducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The simulation findings are compared with the trends of a few of the generated outcomes with the results that had already been published. Georges Atallah [22] estimated the economic feasibility of VRF cooling system and Huang H. et al [23] evaluated the energy saving potential of different insulation materials both found similar trends of energy saving, cost saving and payback periods.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The simulation findings are compared with the trends of a few of the generated outcomes with the results that had already been published. Georges Atallah [22] estimated the economic feasibility of VRF cooling system and Huang H. et al [23] evaluated the energy saving potential of different insulation materials both found similar trends of energy saving, cost saving and payback periods.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the VRF system's energy-saving potential, the expected payback period might be around 1.5 years. Georges Atallah [22] Lifecycle cost analysis was presented to assess the economic viability of CRF (constant refrigerant flow) and VRF (variable refrigerant flow) air conditioning systems. The findings demonstrated that although while the VRF system's initial cost was 23% more than the CRF system's initial cost, the VRF system's present worth cost at the end of its lifetime was significantly lower than the CRF system's due to lower operating costs.…”
Section: Introductionmentioning
confidence: 99%